Pengaruh Kualitas Layanan Mobile Banking Terhadap Kepuasan Nasabah BSI Bertransaksi - Rumaini Rumaini; Abdul Malik; Nurlia Fusfita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Customer satisfaction is the level of one’s feelings after comparing the perceived performance or results with those expected. The purpose of this study aims to find out how partially or simultaneously service quality consisting of Tangible, Reliability, Responsiveness, Assurance, and Empathyon cuctomer satisfaction . In this study, researchers used a descriptive quantitative method. The technique used in sampling in research is non-probability, namely a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as a sample. The questionnaire method used is using a Likert Scale and a sample of 49 respondents. To collect data using a questionnaire and documentation. The data analysis technique used is Data Quality Test, Classical Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis, Coefficient of Determination. The results of the study show that: service quality, namely Tangible (X1), has a significant influence on cuctomer satisfaction. Service quality, namely Reliability (X2) has significant influence on cuctomer satisfaction. Sevice quality, namely Responsiveness (X3) has a significant influence on cuctomer satisfaction. Service quality, namely Assurance (X4) has a significant influence on cuctomer satisfaction. Service quality, namely Empathy (X5) has significant influence on cuctomer satisfaction. Service quality consisting of Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) simultaneously (together) affect cuctomer satisfaction.